A Study on Uric Acid Levels in Non Diabetic Patients at a Tertiary Care Hospital (Academia Journal of Medicine, 2020)
Background: The pathophysiology of diabetic nephropathy is complex and still not fully elucidated. Observational studies suggest a  relationship of UA level with incident CKD, but studies evaluating the relationship with decline in kidney function in established CKD are  conflictingSeveral prospective studies have suggested that hyperuricemia is associated with an increased risk of incident cardiovascular events  and death in both nondiabetic and type 2 diabetic individuals Hyperuricemia also is largely prevalent in patients with chronic kidney  disease(CKD). Subjects and Methods: The patients were randomly divided into two groups according group chosen by time of enrollment.  By using simple random method, 64 study subjects will be taken, and the study subject is divided into 2 groups. A detailed history,  anthropometry, vital signs, clinical examination and laboratory parameters were recorded for both the study group. Results: The Study reveals  that, there was no statistical significant difference of mean serum uric acid among smokers and non-smokers in non-diabetes patients with  CKD (P>0.05).Study reveals that, there was no statistical significant difference of mean serum uric acid among alcoholic and non-alcoholic  cases in non-diabetes patients with CKD (P>0.05). Conclusion: non-diabetic patients with CKD cases (P
Keywords: Hyperuricemia; Nondiabetic; Creatinine